No Evidence for Trade-Offs Between Lifespan, Fecundity, and Basal Metabolic Rate Mediated by Liver Fatty Acid Composition in Birds - Kumar, Sampath A.; Albrecht, Tomáš; Kauzál, Ondřej; Tomášek, Oldřich (Frontiers in Cell and Developmental Biology, 2021)
The fatty acid composition of biological membranes has been hypothesised to be a key molecular adaptation associated with the evolution of metabolic rates, ageing and lifespan—the basis of the membrane pacemaker hypothesis (MPH). MPH proposes that highly unsaturated membranes enhance cellular metabolic processes while being more prone to oxidative damage, thereby increasing the rates of metabolism and ageing. MPH could therefore provide a mechanistic explanation for trade-offs between longevity, fecundity and metabolic rates, predicting that short-lived species with fast metabolic rates and higher fecundity would have greater levels of membrane unsaturation. However, previous comparative studies testing MPH provided mixed evidence regarding direction of covariation between fatty acid unsaturation and lifespan or metabolic rate. Moreover, some empirical studies have suggested that n-3/n-6 PUFA ratio or the fatty acid chain length, rather than the overall unsaturation, could be the key traits co-evolving with lifespan. In this study, we tested the co-evolution of liver fatty acid composition with maximum lifespan, annual fecundity and basal metabolic rate (BMR), using a recently published data set comprising liver fatty acid composition of 106 avian species. While statistically controlling for the confounding effects of body mass and phylogeny, we found no support for long lifespan evolving with low fatty acid unsaturation, and only very weak support for fatty acid unsaturation acting as a pacemaker of BMR. Moreover, our analysis provided no evidence for the previously reported links between lifespan and n-3 PUFA/total PUFA or MUFA proportion. Our results rather suggest that long lifespan evolves with long-chain fatty acids irrespective of their degree of unsaturation as lifespan was positively associated with at least one long-chain fatty acid of each type (i.e. SFA, MUFA, n-6 PUFA and n-3 PUFA). Importantly, maximum lifespan, annual fecundity and BMR were associated with different fatty acids or fatty acid indices, indicating that longevity, fecundity and BMR co-evolve with different aspects of fatty acid composition. Therefore, in addition to posing significant challenges to MPH, our results imply that fatty acid composition does not pose an evolutionary constraint underpinning life-history trade-offs at the molecular level.